The Effect of Compensation and Work Discipline on Employee Performance at PT. Langgeng Baja Pratama in Bekasi Regency - Iryadana, Mohamad Razab (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to determine the effect of compensation and work discipline on employee performance at PT Langgeng Baja Pratama in Bekasi Regency. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study compensation has a significant effect on employee performance of 50.3%, the hypothesis test obtained t count> t table or (7.788> 2.000). Work discipline has a significant effect on employee performance of 41.0%, the hypothesis test obtained t count> t table or (6.462> 2.000). Compensation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.869 + 0.416X1 + 0.353X2 and a contribution of 61.3%, the hypothesis test obtained F count> F table or (46.655> 2.760).